1998
DOI: 10.1210/en.139.3.922
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Is a Mediator of the Inhibitory Effect of Activated Macrophages on Production of Androgen by the Leydig Cell of the Mouse

Abstract: We hypothesized that macrophage activation results in nitric oxide (NO) production and that this NO acts directly on Leydig cells (LC) to alter androgen synthesis. Both peritoneal macrophages and a murine macrophage cell line (RAW 264.7) were activated in vitro by sequential exposure to interferon-gamma (50 U/ml) and then bacterial lipopolysaccharide (LPS; 100 ng/ml) for 24 h each. At various times after initiation of activation, selected wells were harvested for identification of messenger RNA for inducible N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 0 publications
6
68
1
Order By: Relevance
“…60,61 It is believed that NO inhibits the synthesis and release of testosterone from Leydig cells through the inhibition of steroidogenic enzymes, most likely P 450 scc, in a cGMP-independent manner. 6,62 Our current work adds newer perspective to the concept that NO derived from nNOS expressed in Leydig cells may be acting in an autocrine manner to regulate Leydig cell function. Specifically, NO produced from Tn-NOS-positive Leydig cells may act on these same cells as an intercellular and intracellular signaling molecule.…”
Section: Discussionmentioning
confidence: 92%
“…60,61 It is believed that NO inhibits the synthesis and release of testosterone from Leydig cells through the inhibition of steroidogenic enzymes, most likely P 450 scc, in a cGMP-independent manner. 6,62 Our current work adds newer perspective to the concept that NO derived from nNOS expressed in Leydig cells may be acting in an autocrine manner to regulate Leydig cell function. Specifically, NO produced from Tn-NOS-positive Leydig cells may act on these same cells as an intercellular and intracellular signaling molecule.…”
Section: Discussionmentioning
confidence: 92%
“…In the past few years, NO has also emerged as a regulator of multiple functions within the reproductive system (Shukovski & Tsafriri 1995, Bonello et al 1996, Yamauchi et al 1997, and several findings suggest that it may have a significant role in the control of steroidogenesis in both ovary and testes (Adams et al 1992, Welch et al 1995, Olson et al 1996, Hesla et al 1997, Jablonka-Shariff & Olson 1997, Pomerantz & Pitelka 1998, Vega et al 1998.…”
Section: Introductionmentioning
confidence: 99%
“…47 Other studies have demonstrated that the activated macrophage-produced NO is associated with a reduction in the testosterone producing activity in Leydig cells. 48 Notably, this inhibition is at least in part involved with the blockade of the P450 steroidogenic enzymes. 48 In short, the bi-directional relationship manifested by NOS/NO and the hormone/cytokine level is crucial in maintaining the physiological function of the testes.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…48 Notably, this inhibition is at least in part involved with the blockade of the P450 steroidogenic enzymes. 48 In short, the bi-directional relationship manifested by NOS/NO and the hormone/cytokine level is crucial in maintaining the physiological function of the testes.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%